Reliability and Reproducibility of Hadamard Encoded Pseudo-Continuous Arterial Spin Labeling in Healthy Elderly - Neumann, Katja; Schidlowski, Martin; Günther, Matthias; Stöcker, Tony; Düzel, Emrah (Frontiers in Neuroscience, 2021)
The perfusion parameters cerebral blood flow (CBF) and arterial transit time (ATT) measured with arterial spin labeling (ASL) magnetic resonance imaging (MRI) provide valuable essentials to assess the integrity of cerebral tissue. Brain perfusion changes, due to aging, an intervention, or neurodegenerative diseases for example, could be investigated in longitudinal ASL studies with reliable ASL sequences. Generally, pseudo-continuous ASL (pCASL) is preferred because of its larger signal-to-noise ratio (SNR) compared to pulsed ASL (PASL) techniques. Available pCASL versions differ regarding their feature details. To date only little is known about the reliability and reproducibility of CBF and ATT measures obtained with the innovative Hadamard encoded pCASL variant, especially if applied on participants in old age. Therefore, we investigated an in-house developed Hadamard encoded pCASL sequence on a group of healthy elderly at two different 3 Tesla Siemens MRI systems (Skyra and mMR Biograph) and evaluated CBF and ATT reliability and reproducibility for several regions-of-interests (ROI). Calculated within-subject coefficients of variation (wsCV) demonstrated an excellent reliability of perfusion measures, whereas ATT appeared to be even more reliable than CBF [e.g., wsCV(CBF) = 2.9% vs. wsCV(ATT) = 2.3% for a gray matter (GM) ROI on Skyra system]. Additionally, a substantial agreement of perfusion values acquired on both MRI systems with an inter-session interval of 78 ± 17.6 days was shown by high corresponding intra-class correlation (ICC) coefficients [e.g., ICC(CBF) = 0.704 and ICC(ATT) = 0.754 for a GM ROI]. The usability of this novel Hadamard encoded pCASL sequence might improve future follow-up perfusion studies of the aging and/or diseased brain.